Two new species of the genus Goniurosaurus (Squamata: Sauria: Eublepharidae) from southern China - Yang, Jian-Huan; Chan, Bosco Pui-Lok (Zootaxa, 2015)
Two new species of large geckos in the genus Goniurosaurus are described based on specimens collected from karst areas of Guangxi Zhuang Autonomous Region, southern China: Goniurosaurus kadoorieorum sp. nov. and Goniurosaurus kwangsiensis sp. nov. Data on natural history of the new species are provided, as well as discussions on the current conservation status of Goniurosaurus species in southern China. Due to the popularity of this genus as novelty pets, and recurring cases of scientific descriptions driving herpetofauna to near-extinction by commercial collectors, we do not disclose the collecting localities of these restricted-range species in this publication. However, such information has been presented to relevant government agencies, and is available upon request by fellow scientists.